2019
DOI: 10.1111/ijd.14751
|View full text |Cite
|
Sign up to set email alerts
|

Statin‐induced dermatomyositis for the practicing dermatologist: a review of the literature

Abstract: Statins cause a spectrum of muscle-related adverse events, including autoimmune myopathies such as dermatomyositis (DM). This review aims to describe the events of statin-induced DM and amyopathic dermatomyositis (ADM) to increase awareness for practicing dermatologists about harmful interactions with the most commonly prescribed lipid-lowering medication. PubMed was searched for relevant literature related to statininduced DM and ADM. Numerous cases of statin-induced DM have been reported in individuals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…These scores may be skewed lower given the number of cases with cancer as a possible cause for DM. Reference lists of 114 eligible articles revealed 20 additional articles that were included. Among 134 articles, data from 165 patients were included in the systematic review (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…These scores may be skewed lower given the number of cases with cancer as a possible cause for DM. Reference lists of 114 eligible articles revealed 20 additional articles that were included. Among 134 articles, data from 165 patients were included in the systematic review (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Autoimmune necrotizing myositis [10][11][12]138] is a feared complication of statin use. (Other autoimmune complications of statins are also reported [139][140][141][142][143]-which can affect muscle [144][145][146][147]-and in some cases, these accompany autoimmune myositis [13][14][15][16]148].) Autoimmunity is also a complication of COVID-19 [149][150][151][152] (encompassing, specifically, autoimmune conditions reported with statins [6,7,[153][154][155] including necrotizing myositis [8,9]) and is a factor in long-COVID [156][157][158][159]: in one "multi-omics" study of long-COVID, an autoimmune profile represented one of the four key patterns observed [160].…”
Section: Skeletal Muscle (Airway Dilator Muscles and Muscles Of Respi...mentioning
confidence: 99%
“…Statins are the most common hypolipidemic drugs in the world, and they are also primary and secondary preventive drugs for people at risk of cardiovascular disease 4 . Statin-induced myopathy is relatively common, but it is usually mild, with only a small proportion presenting as rhabdomyolysis 5–7 . Patients with rhabdomyolysis vary in severity, ranging from asymptomatic elevated serum CK, muscle pain, and myoglobinuria to life-threatening diseases 8 .…”
mentioning
confidence: 99%
“…4 Statin-induced myopathy is relatively common, but it is usually mild, with only a small proportion presenting as rhabdomyolysis. [5][6][7] Patients with rhabdomyolysis vary in severity, ranging from asymptomatic elevated serum CK, muscle pain, and myoglobinuria to life-threatening diseases. 8 This case demonstrates that rhabdomyolysis should be included in the differential diagnosis of muscle symmetrical and diffuse uptake of tracer and 68 Ga-FAPI PET/CT may have the potential to evaluate the extent and severity of rhabdomyolysis.…”
mentioning
confidence: 99%